MARKETING STRATEGIES FOR BANKING SERVICE AND THEIR IMPACT ON ATTRACTING INVESTORS AND ACHIEVING FINANCIAL GROWTH - Ali faron abd; Ilham Ghanim Hasan (Scholars Digest Publishing, 2024)
The bank is an economic enterprise that needs to attract more customers for growth and development, so it is necessary to put the marketing strategy of banking services on the agenda. This research was conducted in a quantitative-inductive way and its purpose was to study the effect of marketing strategy of banking services on attracting investors and financial growth. A researcher-made questionnaire with acceptable validity and reliability was used and each variable was measured with five items. The statistical population was the customers of Pasargad Bank, after sending SMS, finally 150 people agreed to fully cooperate with the researcher. All three hypotheses of the research were proven with 99% certainty and it can be said that in the case of a successful marketing strategy of banking services, direct and indirect investments in the bank have increased and as a result the bank's financial resources have increased, which ultimately leads to financial growth.
Keywords: Marketing strategy, Banking services, Bank investment, Financial growth.